A Tale of Two Patient Safety Programs: Comparing Tools and Skills in Two Programs for Integration into Interprofessional Clinical Simulation-Based Training. (November 2019) - Kennel, Victoria; Fedderson, Julie; Skinner, Nicole; Lowndes, Bethany
Patient safety improvement efforts across the country intend to address the threat of medical errors that lead to patient morbidity and mortality. Many hospital-based patient safety programs focus on team tools and skills to support the interdisciplinary nature of healthcare delivery. This institution utilizes two patient safety programs with different groups of professionals and medical trainees. The aim of our research was to identify tool and skill compatibility between the two programs for future integration into interprofessional clinical simulation-based training experiences. Two researchers conducted an independent content analysis of the tools and skills in the two programs to: 1) identify the similarities and differences among tools and skills, and, 2) categorize their potential for integration into clinical simulation-based training. The two programs had six common tools, a majority of which were communication-based. Over half the tools were team-focused. Five common team tools (Brief, SBAR, Check-Back, CUS, and Debrief) were identified for integration in interprofessional clinical simulation-based training experiences.